Roles and Clinical Application of Exosomes in Prostate Cancer - Hu, Guangmo; Xie, Lingui; Zhou, Yibin; Cai, Xiaowei; Gao, Peng; Xue, Boxin (Frontiers in Urology, 2022)
Prostate cancer is the second most frequent cancer type among men globally. Herein, the roles of exosomes in prostate cancer tumorigenesis, progress along with metastasis were reviewed. Exosomes are small extracellular vesicles originated from the endosomal system then released to surrounding body fluids. They carry cargo comprising nucleic acids and proteins and deliver then to recipient cells and are implicated in cell-to-cell communications. They regulate the activities of recipient cells by modulating several physiological and pathological processes, such as remodeling the properties of the tumor microenvironment, modulating cancer metabolism and metastases, and regulating drug resistance. Tumor derived exosomes are present in various body fluids and their molecular profile can reflect the real-time status of the cancer cell. These characteristics make them prospective biologic signatures for diagnosis along with prognosis of different cancer types. Besides, exosomes have good biophysical properties, for instance high stability in the lipid bilayer membrane, as well as low immunogenicity which are key parameters for development of novel drug delivery approach.